The anti-inflammatory properties of vinpocetine mediates its therapeutic potential in management of atherosclerosis - Abdullah A. Alshehri; Hayder M. Al-kuraishy; Ali I. Al-Gareeb; Sabrean F. Jawad; Wael Y. Khawagi; Athanasios Alexiou; Marios Papadakis; Abdullah A Assiri; Heba Elhadad; Gaber El-Saber Batiha (BMC, 2024)
Abstract Atherosclerosis (AS) formation is enhanced by different mechanisms including cytokine generation, vascular smooth muscle cell proliferation, and migration. One of the recent treatments towards endothelial dysfunction and AS is Vinpocetine (VPN). VPN is a potent inhibitor of phosphodiesterase enzyme 1 (PDE-1) and has anti-inflammatory and antioxidant effects through inhibition the expression of nuclear factor kappa B (NF-κB). VPN has been shown to be effective against the development and progression of AS. However, the underlying molecular mechanism was not fully clarified. Consequently, objective of the present review was to discuss the mechanistic role of VPN in the pathogenesis AS. Most of pro-inflammatory cytokines that released from macrophages are inhibited by action of VPN through NF-κB-dependent mechanism. VPN blocks monocyte adhesion and migration by constraining the expression and action of pro-inflammatory cytokines. As well, VPN is effective in reducing of oxidative stress a cornerstone in the pathogenesis of AS through inhibition of NF-κB and PDE1. VPN promotes plaque stability and prevents the erosion and rupture of atherosclerotic plaque. In conclusion, VPN through mitigation of inflammatory and oxidative stress, and improvement of plaque stability effects could be effective agent in the management of AS.